A longitudinal study of differences in late and early onset geriatric depression: Depressive symptoms and psychosocial, cognitive, and neurological functioning - Sachs-Ericsson, Natalie (2012)
OBJECTIVES: Studies suggest early onset depression (EOD) is associated with a more severe course of the depressive disorder, while late onset depression (LOD) is associated with more cognitive and neuroimaging changes. This study examined if older adults with EOD, compared with those with LOD, would exhibit more severe symptoms of depression and, consistent with the glucocorticoid cascade hypothesis, have more hippocampal volume loss. A second goal was to determine if LOD, compared with EOD, would demonstrate more cognitive and neuroimaging changes. METHOD: At regular intervals over a four year period non-demented, older, depressed adults were assessed on the Mini Mental Status Examination (MMSE) and the Montgomery-Asberg Depression Rating Scale (MADRS). They were also assessed on Magnetic Resonance Imaging (MRI). RESULTS: Compared with LOD, EOD had more depressive symptoms, more suicidal thoughts, and less social support. Growth curve analyses indicated that EOD demonstrated higher levels of residual depressive symptoms over time. The LOD group exhibited a greater decrement in cognitive scores. Contrary to the glucocorticoid cascade hypothesis, participants with EOD lost right hippocampal volume at a slower rate than did participants with LOD. Right cerebrum gray matter was initially smaller among participants with LOD. CONCLUSIONS: EOD is associated with greater severity of depressive illness. LOD is associated with more severe cognitive and neurological changes. These differences are relevant to understanding cognitive impairment in geriatric depression.